Severe Postoperative Chronic Constipation Related to Anorectal Malformation Managed with Osteopathic Manipulative Treatment - Vismara, Luca (Case Rep Gastroenterol, 2020)
Constipation is frequent amongst infants who have undergone surgery for anorectal malformation (ARM). Faecal retention, due to a dysfunctional enteric reflex of defaecation, can cause abdominal cramps, pseudoincontinence and, in the worst cases, megacolon. Prokinetic protocols are used to stimulate at least 1 bowel movement per day, including laxatives, enema, stools softeners and dietary schedules. While osteopathic manipulative treatment is adopted in adults for functional constipation, it has not been described for infants. Herein, we report the case of an infant undergoing anorectoplasty for a low ARM who was referred to the osteopath 2 years after the onset of severe constipation associated with pseudoincontinence and abdominal cramps and was refractory to the prokinetic protocol. In a child with a good ARM prognosis, autonomous daily bowel movements should be achieved. In this child, the imbalanced tension of the pelvic floor and immaturity of the parasympathetic plexus led to a functional alteration of the defaecation reflex. After adjunction of osteopathic manipulative treatment (OMT) to the therapeutic panel, the constipation showed gradual remission, with acquisition of autonomous defaecation 4 months after the therapy began. This suggests the importance of investigating the efficacy of OMT inclusion in the postsurgical prokinetic protocols for ARM patients with a good prognosis.